The S-layer Associated Serine Protease Homolog PrtX Impacts Cell Surface-Mediated Microbe-Host Interactions of Lactobacillus acidophilus NCFM - Johnson, Brant R.; O’Flaherty, Sarah; Goh, Yong Jun; Carroll, Ian; Barrangou, Rodolphe; Klaenhammer, Todd R. (Frontiers in Microbiology, 2017)
Health-promoting aspects attributed to probiotic microorganisms, including adhesion to intestinal epithelia and modulation of the host mucosal immune system, are mediated by proteins found on the bacterial cell surface. Notably, certain probiotic and commensal bacteria contain a surface (S-) layer as the outermost stratum of the cell wall. S-layers are non-covalently bound semi-porous, crystalline arrays of self-assembling, proteinaceous subunits called S-layer proteins (SLPs). Recent evidence has shown that multiple proteins are non-covalently co-localized within the S-layer, designated S-layer associated proteins (SLAPs). In Lactobacillus acidophilus NCFM, SLP and SLAPs have been implicated in both mucosal immunomodulation and adhesion to the host intestinal epithelium. In this study, a S-layer associated serine protease, PrtX (prtX, lba1578), was deleted from the chromosome of L. acidophilus NCFM. Compared to the parent strain, the PrtX-deficient strain (∆prtX) demonstrated increased autoaggregation, an altered cellular morphology, and pleiotropic increases in adhesion to mucin and fibronectin, in vitro. Furthermore, ∆prtX demonstrated increased in vitro immune stimulation of IL-6, IL-12, and IL-10 compared to wild-type, when exposed to mouse dendritic cells. Finally, in vivo colonization of germ-free mice with ∆prtX led to an increase in epithelial barrier integrity. The absence of PrtX within the exoproteome of a ∆prtX strain caused morphological changes, resulting in a pleiotropic increase of the organisms’ immunomodulatory properties and interactions with some intestinal epithelial cell components.